Rosetown - Rylant, Cynthia (New York : Beach Lane Books, 2018)
In 1972, Flora Smallwood, nine, copes with her parents' separation with the help of her friends, Yury and Nessie, a new pet, and the familiar routines of life in Rosetown, Indiana.
Ages 8-12.
Keywords: Friendship -- Fiction; Family life -- Indiana -- Fiction; City and town life -- Fiction; Books and reading -- Fiction; JUVENILE FICTION / Social Issues / General (see also headings under Family).; JUVENILE FICTION / Girls & Women; JUVENILE FICTION / Social Issues / Friendship; Indiana -- History -- 20th century -- Fiction